Four Steps Block Predictor-Block Corrector Method for the solution of y"=f(x,y,y) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
A method of collocation and interpolation of the power series approximate solution at some selected grid points is considered to generate a continuous linear multistep method with constant step size.predictor-corrector method was adopted where the predictors and the correctors considered two and three interpolation points implemented in block method respectively.The efficiency of the proposed method was tested on some numerical examples and found to compete favorably with the existing methods.